Pelatihan Penerapan Model-model Pembelajaran Inovatif untuk Meningkatkan Kompetensi Pedagogik Guna Pengembangan Keprofesian Berkelanjutan Bagi Guru-guru SD Gugus 3 Palu Utara - Murdiana, I Nyoman; Sukayasa, Sukayasa; Hasbi, Muh.; Karniman, Tegoeh S. (Jurnal Kreatif Online, 2020)
Teachers are required to be able to carry out self-development sustainably through Sustainable Professional Development (PKB) activities. One of the PKB activities is to conduct research, especially Action Research (PTK). In doing PTK is very much determined by the ability to carry out innovative learning. The results of interviews with the Head of Teacher Working Group (KKS) of Gugus 3 Palu Utara obtained information that there are still many teachers in the Gugus 3 Palu Utara District experiencing problems in implementing Student Center-based Learning (SCL) models that match the expectations of Kurikulum 13 (K13). This community service was intended to provide training to teachers of SD Gugus 3 Palu Utara in the application of innovative SCL-based learning models that are in accordance with the K13 paradigm in order to improve pedagogical abilities in the context of sustainable professional development. During the implementation of the training activities, the teachers of SD Gugus 3 Palu Utara showed high enthusiasm in participating in this training activity and many of them asked questions about things they did not clearly understand. This indicated that the implementation of the training received positive responses from the teachers of SD Gugus 3 Palu Utara. From the results of the distribution of service instruments, it was found that the average percentage of participants who answered correctly was 88%, it meant that the training participants' mastery of innovative learning was very good.